PENINGKATAN KETERAMPILAN MENGKOMUNIKASIKAN DAN MENYIMPULKAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM SOLVING - Erika Mirna Sari; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2013)
This research aimed to describe the Problem Solving learning model that are effective in improving the communication and the inferen skills on Redoks Reaction material. The sampling technique used purposive sampling technique. This research use a quasi-experimental methods with Non Equivalent (Pretest and Posttest) Control Group Design. The sample in this research is students of State Senior High School Yadika in Bandar Lampung and obtained X 3 and X 5 class at school year 2012-2013 which has almost the same characteristics. The effectiveness of Problem Solving learning model measured on the difference and the improvement of a significant N-gain. The results showed the average value of N-gain communication skills for control class and experiment class are 0,44 and 0.62, and the average value of N-gain inferen skills for control class and experiment class are 0.45 and 0.60. Based on the test of the hypothesis, it is known that a class with Problem Solving learning model has the communication and the inferen skills higher than conventional class learning. This showed that the Problem Solving learning was more effective in improving the communication and the inferen skills.Kata kunci: pembelajaran problem solving, keterampilan mengkomunikasikan, keterampilan menyimpulkan.